The revealing : a novel - Fisher, Suzanne Woods (Fisher, Suzanne Woods. Inn at Eagle Hill, 2014)
Naomi King--soft spoken, loyal, and easily overlooked--has a gift. She sees what others can't see. Intuition, she calls it. Others in Stoney Ridge don't know what to make of it and dismiss her hunches and inklings altogether. When a young woman arrives at the Inn at Eagle Hill with a shocking secret about Tobe Schrock, Naomi fears the worst. She can't ignore the feeling that something sinister's at work--something more than a threat to the tenuous love begun between Tobe and her.